Use of Antioxidants in Chicken Nuggets Manufactured with and Without the Use of Salt and/or Sodium Tripolyphosphate: Effects on Product Quality and Shelf-life Stability - O`Sullivan, Clare Maria; Lynch, Anna-Marie; Lynch, Patrick Brendan; Buckley, Denis Joseph; Kerry, Joseph Patrick (International Journal of Poultry Science, 2004)
Nuggets were manufactured from equal portions of breast and thigh chicken meat from chickens fed either a basal (control) or a supplemented level of alpha-tocopheryl acetate (vitamin E). Rosemary (0.10%) (R), sage (0.10%) (S) and tea catechins (0.01%) (TC), which were chosen from previous screening trials, were added to both control and vitamin E meat from which chicken nuggets were manufactured. The trial was repeated twice more where in addition to antioxidant addition to meat prior to nugget manufacture, 0.75% salt and 0.75% salt and 0.25% sodium tripolyphosphate (STPP) were also incorporated into both control and supplemented minced meat. Nuggets were tested for oxidative (TBARS) stability, colour (Hunter ´L, a, b` values) stability and percentage cook loss. There was a synergism between vitamin E and added antioxidants as nuggets containing vitamin E with R, S or TC had lower TBARS values than those containing vitamin E alone. Control nuggets containing R, S and TC had lower (p<0.01) TBARS than the control without antioxidants. R, S and TC functioned as antioxidants in the presence of salt, during refrigerated (4°C) storage for both control and vitamin E meat. The increase in TBARS numbers caused by the addition of salt was reduced by the inclusion of STPP in the chicken nugget formulation. Hunter ´a` values of nuggets formed without the use of salt or STPP were lower than those of nuggets formed with salt or salt and STPP. For nuggets containing 0.75% salt, Hunter ´a` values were highest for those manufactured from control meat without antioxidants. Nuggets containing S had lower (p<0.05) Hunter ´a` values than all other groups on days 3 and 6. In conclusion, the use of antioxidants reduced lipid oxidation in chicken nuggets both in the presence and absence of salt. However, when STPP was incorporated into the same product system the effect of antioxidants was reduced to a significant degree.